2021
DOI: 10.30910/turkjans.980819
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Carbonic Anhydrase Inhibitory Effects of The Extracts of Satureja cuneifolia

Abstract: Carbonic anhydrases catalyze the interconversion between carbon dioxide and bicarbonate. Carbonic anhydrase inhibition has therapeutic importance and there are many drugs which use this mechanism. Carbonic anhydrase inhibitors are used as diuretic, antiglaucoma, antitumor and antiepileptic agents. As an alternative for synthetic chemicals with strong side effects, natural products have gained popularity in the recent years. In this study, Satureja cuneifolia, a medicinal plant used as folk medicine, was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…The H. lippii fractions also displayed appreciable potential except for the DCM and MeOH extracts, while aqueous extract was most potent presented IC 50 = 9:9 ± 0:35 μg/mL, proceeded by the nhexane with IC 50 = 18:8 ± 3:13 μg/mL and IC 50 = 35:6 ± 1:32 μg/mL in comparison to the standard acetazolamide having an IC 50 = 4:04 ± 1:63 μg/mL. The current results also match up with the outcomes of Aydin et al [69] for Satureja cuneifolia and dodoneine by Carreyre et al [70] which was found effective for the carbonic anhydrase activity. However, the study reported for the bioactive ingredient dodoneine by Carreyre et al [70] was significant as compared to our current findings because might be bioactive compounds are responsible compounds as compared to our selected plants and tested fractions…”
Section: Antidiabetic Significancesupporting
confidence: 90%
“…The H. lippii fractions also displayed appreciable potential except for the DCM and MeOH extracts, while aqueous extract was most potent presented IC 50 = 9:9 ± 0:35 μg/mL, proceeded by the nhexane with IC 50 = 18:8 ± 3:13 μg/mL and IC 50 = 35:6 ± 1:32 μg/mL in comparison to the standard acetazolamide having an IC 50 = 4:04 ± 1:63 μg/mL. The current results also match up with the outcomes of Aydin et al [69] for Satureja cuneifolia and dodoneine by Carreyre et al [70] which was found effective for the carbonic anhydrase activity. However, the study reported for the bioactive ingredient dodoneine by Carreyre et al [70] was significant as compared to our current findings because might be bioactive compounds are responsible compounds as compared to our selected plants and tested fractions…”
Section: Antidiabetic Significancesupporting
confidence: 90%